The effects of one session of roller massage on recovery from exercise-induced muscle damage: A randomized controlled trial - Flávia V.A. Medeiros; Martim Bottaro; Wagner R. Martins; Deise L.F. Ribeiro; Emmanuela B.A. Marinho; Ricardo B. Viana; João B. Ferreira-Junior; Jake C. Carmo (Elsevier, 2020)
Background/objective: Roller massage has become a popular intervention in sports settings in order to treat muscle soreness and stiffness, as well as improving post-exercise recovery, although there is limited evidence for these assumptions. Therefore, the purpose of this study was to evaluate the effects of a single session of roller massage, applied with a controlled force after an exercise-induced muscle damage protocol, on muscle recovery. Methods: A randomized controlled study was performed using a repeated-measures design. Thirty-six young men completed four sets of six eccentric actions of elbow flexors at 90°/s with a 90s rest interval between sets. Participants were randomly assigned into one of three groups: 1) Roller massage (n = 12), 2) Sham (n = 12), and 3) Control (n = 12). Maximal isometric voluntary contraction (MIVC), delayed-onset muscle soreness (DOMS), range of motion (ROM), and muscle thickness were measured at baseline, and at 24, 48, and 72 h post exercise. Results: There was no significant group by time interaction for MIVC (p = 0.090) and ROM (p = 0.416). Also, although there was a significant group by time interaction for muscle thickness (p = 0.028), post hoc test did not find significant difference between groups (p > 0.05). DOMS was recovered at 72 h for roller massage (p < 0.001) and control (p < 0.001) groups, while the Sham group did not recover from DOMS across 72 h (p < 0.001). There was also no significant difference between groups in DOMS at any time (p > 0.05). Conclusions: A single session of roller massage applied on elbow flexors had no effect on recovery of MIVC, muscle swelling, ROM and DOMS.